Structures d’information et décision en équipe dans le système de distribution des soins - Haurie, Alain (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractIn this paper one proposes a methodological framework for the study of information and decision structures in hospital management. With a particular reference to the control of nursing care demand and supply, various information and decision schemes are considered.The concepts of disease dynamics, state of the hospital system, information, strategy are explored. It is shown how recent theoretical results dealing with the economics of information or team decision theory may serve to formulate and analyse some fundamental resource allocation problems.